Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 463: 115



Work Step by Step

$6x^{4}+35x^{2}-6$ ... Searching for two factors of $ac=-36$ whose sum is $b=35,$ we find$\qquad 36$ and $-1.$ Rewrite the middle term and factor in pairs: $=6x^{4}+36x^{2}-x^{2}-6=$ $=6x^{2}(x^{2}+6)-(x^{2}+6)$ =$(x^{2}+6)(6x^{2}-1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.